2014
DOI: 10.1051/0004-6361/201322372
|View full text |Cite
|
Sign up to set email alerts
|

JointPlanckand WMAP CMB map reconstruction

Abstract: We present a novel estimate of the cosmological microwave background (CMB) map by combining the two latest full-sky microwave surveys: WMAP nine-year and Planck PR1. The joint processing benefits from a recently introduced component separation method coined "local-generalized morphological component analysis" (LGMCA) and based on the sparse distribution of the foregrounds in the wavelet domain. The proposed estimation procedure takes advantage of the IRIS 100 μm as an extra observation on the galactic center f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 30 publications
2
116
0
Order By: Relevance
“…• we removed the cosmological CMB and KSZ signals subtracting the LGMCA CMB template [54,55] at each Planck channel. It has been previously demonstrated that this step does not introduce any distortion to the TSZ emission [32];…”
Section: B Foreground Cleaned Planck Nominal Mapsmentioning
confidence: 99%
“…• we removed the cosmological CMB and KSZ signals subtracting the LGMCA CMB template [54,55] at each Planck channel. It has been previously demonstrated that this step does not introduce any distortion to the TSZ emission [32];…”
Section: B Foreground Cleaned Planck Nominal Mapsmentioning
confidence: 99%
“…This choice was motivated by the contamination of the Planck official CMB maps by tSZ residuals (see e.g. Bobin et al 2014), which would bias our analysis. We also show in Sect.…”
Section: Datamentioning
confidence: 99%
“…Planck has effectively imaged CMB temperature modes at scales < 2000 to nearly the cosmic variance limit (even if considering a foreground cleaned map like SMICA [57] or LGMCA [12,13]). The CMB halo lensing signal can be contaminated by both noise and systematic biases from cluster foregrounds such as tSZ and CIB.…”
Section: Cmb Halo Lensingmentioning
confidence: 99%